Diagnóstico do dano físico e social após a alta medicamentosa das pessoas que tiveram hanseníase - Nardi, Susilene Maria Tonelli (2012)
Introduction: Leprosy is a chronic infectious, contagious, insidious, but treatable disease that causes dermatoneurologic disorders. The complications resulting from neurological involvement cause sequelae that often affect the eyes, nose, hands and feet and if not treated early, evolve to physical disabilities that are sometimes irreversible and disastrous for the functionally of the individual. In Brazil, the coefficient of severe and visible physical disabilities (Grade 2) at diagnosis is considered high (≥ 10) by the Ministry of health. The drug treatment that eliminates the bacillus does not guarantee the end of the progression of the disability. Thus, ex-patients with severe or mild physical disabilities should remain under the care of a rehabilitation team. Aim: To assess physical disabilities, social participation and activity limitations of individuals affected by leprosy after completing multidrug therapy, describing their relationship with the socio-demographic characteristics of these individuals and estimate the distances between their homes and rehabilitation services. Patients and methods: A cross-sectional descriptive study was carried out of all leprosy patients from 1998 to 2006 who were residents and treated in São José do Rio Preto, SP, Brazil. A specific questionnaire was applied to obtain general and clinical data. The physical disabilities were assessed using the Degree of Disability score of the WHO and the Eyes-Hand-Feet score. The Screening of Activity Limitation and Safety Awareness scale (SALSA) and the scale of participation (version 4.6) were applied to measure social participation. Results: Of the 335 people treated in the period, 223 (66.6%) were contacted and evaluated. Of these, 51.6% were women, the mean age was 54 years (SD 15.7), 66.4% had up to 6 years of schooling, 43.5% worked and 26.9% were retired, and the dimorphous form of the disease predominated (39.9%). The mental and physical healths were considered good in the previous month by 50.2% and 59.2% of the participants, respectively. Pain was reported by 54.7% of respondents; 54.3% suffered from some disease. Disabilities occurred in 32% and limitations of activities as evaluated by the SALSA scale affected 57.8% the participants. Restrictions in social participation occurred in 35.4% of the ex-patients. The presence of disabilities was higher with increasing age, in cases of multibacilar disaease and when individuals considered their physical health was bad. Those who needed preventive measures/rehabilitation travelled a mean distance of 5.5 km to the rehabilitation service. There were significant associations of social restriction with family income of less than 3 minimum wages, associated diseases, hospitalization within the previous year and physical disabilities. There were also associations of activity limitations with being female, household income ≤ 3 minimum wages, reports of significant injury, pain, associated diseases and physical disability. Conclusions: Disabilities are common and were associateed with increasing age, the multibacilar form of the disease and the feeling that the physical health was bad. Social restriction was also common and influenced by the presence of deficiencies, associated diseases, recent hospitalization and low income. The limitation of activities was more common than physical disabilities, and was associated to low incomes, being female, presence of injury, disability, disease and pain. Rehabilitation services are far from patients residences.